TOURISTS’ BEHAVIORS IN VISITING BUDDHIST TEMPLES IN YOGYAKARTA BASED ON GENDER DIVERSITY - Shadikah, Arina Afiyati (STAH Dharma Sentana Sulawesi Tengah, 2024)
This research was conducted in Yogyakarta esecially at the Buddhist Temples namely Sewu Temple, Banyunibo Temple, Kalasan Temple, and Sari Temple. This research aimed to investigate tourists’ behavior in visiting those Buddhist temples. There were some related researches to the previous study. However, the gap was found. It is about the gender difference towards their behaviors. There was a qualitative research design employed in this study. There were two data collection techniques used to collect the data. They were tourists’ behavior questionnaires and interview. The data gathered were analyzed using a research design called flow method of qualitative design. This research method consisted of four stages, those namely collecting data, reducing data, displaying data, and concluding or verifying. The result of this study indicated that: (1) there were five behaviors did by the tourists, namely commercial transaction, social interaction, activities preference, bargaining, and knowledge of destination (2) the female tourists had more behaviors in visiting Buddhist temples than the male tourists did.